MENINGKATKAN PERKEMBANGAN MOTORIK HALUS MELALUI KEGIATAN FINGER PAINTING PADA ANAK USIA DINI - Rima (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2024)
Children's fine motor skills in kindergarten. Santa Maria Regina has not developed optimally, especially in the activities of moving her fingers or the ability to grasp and hold objects. Based on these problems, researchers are interested in implementing finger painting activities to improve children's fine motor skills, because through finger painting activities children's fingers will move and rub against the coloring paint. The aim of this research is to improve fine motor skills through finger painting activities in kindergarten. Santa Maria Regina, Raja Ampat Regency. This type of research is classroom action research which is carried out through 2 cycles, namely including planning, implementation, observation, and reflection. Based on the results of research that has been carried out, it is known that finger painting activities can improve children's fine motor skills at Santa Maria Regina Kindergarten. This can be seen from the results of the second cycle assessment which shows that fine motor skills have reached the expected development criteria, namely BSH (Developing According to Expectations). This can also be seen during the finger painting process, children are able to coordinate their eyes and hands. This can be seen from the child being able to use his hands and fingers to paint well and the child's fingers seem flexible during painting activities.